Ethnic minority visitors and non-visitors: an examination of constraints regarding outdoor recreation participation in Rocky Mountain National Park - Roberts, Nina S., author; Rogriguez, Donald A., advisor; Bright, Alan, advisor; Berry, Joyce, committee member; Pickering, Kathy, committee member (Colorado State University. Libraries, 2003)
Empirical research directed at outdoor recreation experiences of ethnic minorities and national parks is on the rise yet still remains largely unexplored. Despite an increasing amount of research on constraints, in particular, it is common knowledge that people of diverse cultures still do not fully experience the range of outdoor recreational opportunities that abound in Western public lands. Rocky Mountain National Park (RMNP) receives over three million visitors annually; although various diversity initiatives have achieved some notable successes, ethnic minorities and individuals from low socioeconomic backgrounds continue to be underrepresented in outdoor recreation participation. Previous studies have addressed activity preferences across different races, examined the relationship between race and recreation setting preferences and behaviors, and explored general constraints to participation. While results have varied considerably, few have collectively examined how ethnicity (i.e., beyond "race") can shape attitudes, perceptions and experiences with constraints to recreation participation in natural areas, and what is the influence of one's culture on these perceptions and experiences. Using a multi-method approach (consisting of a Delphi technique, focus group interviews, and mail back survey), this study explored constraints experienced by African American and Latino visitors and non-visitors to RMNP in particular, and to National Parks in general. The issue of perceived discrimination embedded in institutional practices and among white park visitors, and opinions of minority resource professionals were also considered integral to this project. Total participants consisted of 175 African Americans and Latinos residing along the Front Range in Colorado. The Delphi procedure was conducted involving a nationwide panel of experts (e.g., "key informants") representing minority resource professionals. Six focus groups were then conducted at different time frames with individuals from specific racial backgrounds participating together in order to maintain group cohesion. Questions developed for the third and final mail back survey phase were generated from results of the first two phases as well as from previously tested instruments. The survey was then subjected to rigorous peer review, pre-testing, and approval from the National Park Service Social Science program. Cluster analysis resulted in the classification of three clusters of individuals based on ten constraint dimensions; secondary analyses were also used to test other relationships of interest. Results of the study indicate that while ethnicity and culture influenced visitor attitudes and non-visitor perceptions in how they experienced a variety of constraints, gender and income had a greater impact. That is, while there is a definite connection for many individuals, collectively ethnicity was not a principal determinant of constraints to visitation. Taken together, all three methods resulted in six primary categories of common constraints: Culture of the National Park Service, perceived discrimination, historical context, discomfort/safety, socialization (e.g., at an early age and 'social permission' from peers), and lack of knowledge and awareness. Recommendations for management and implications for future research are discussed. Recognizing the depth of constraints perceived or experienced by ethnic minority communities should assist park managers in understanding what constraints are most salient in shaping various attitudes and perceptions; accordingly, managers can strive to reduce constraints as best as possible through effective communication and outreach.
Keywords: minority and ethnic groups; sociology; recreation; ethnic studies